Bio-based lubricants for forming of magnesium. (August 2015) - Ramezani, Maziar; Schmid, Steven R.
Abstract: For a number of reasons, magnesium is being used increasingly often in applications where weight savings are desired. However, magnesium is difficult to form, so that warm or hot forming are generally necessary. Lubricants are recognized as essential in these processes, but the lubricants used to date for magnesium forming have environmental drawbacks. This paper evaluates the tribological behavior and rheology of four types of bio-based metal working fluids. Using an elastohydrodynamic lubrication apparatus, their traction behavior was measured and their piezoviscous behavior was determined by applying the well-known Hamrock–Dowson equation to measured film thickness profiles. The results showed that the investigated bio-lubricants have good ability to generate lubricant films in forming of magnesium. Traction tests showed low friction values, indicating the investigated bio-lubricants are suitable for metal forming applications where effective lubrication is desired.